Justiça restaurativa como novo paradigma de justiça na vara de execução de penas alternativas de João Pessoa-PB - Alves, Juliana Guedes (2016)
Developments in conflict resolution practices appears necessary before the increase in lawsuits, criminal justice that is unleashed on the need to ward off discredited criminal justice. Restorative Justice is presented at this juncture in order to humanize the practice of criminal justice. However, back to attract the involvement of the victim in the search repair, offering you from your interests and taking the offender to build the culture of accountability. This paper aims to clarify the need to build this new justice model, adapting it to the reality of the Court of Execution of Penalties João Pessoa Alternative (VEPA-JP). For this turns the work the perception of the problems and reality stick. Portrays the difficulties to be overcome, and security strategies necessary for the JR is inclusion tool protection and defense of human rights, away from the autotutela and leading the national drive to achieve its inclusive social function, approaching safely victim and offender. Attributed to restrictive penalty law the possibility of its use for building culture of accountability, away from the stigma of impunity, as though that this is judicial execution, society does not recognize it as proportional to criminal redress. At work Restorative justice is seen by innovative perspective of empowering the victim because satifaction is offered by the possibility of the victim to monitor compliance with the penalty or receive it directly in your favor, approaching the offender to know their reality and help him to realize the damage that this has caused and its consequences, blaming it.